A Review to Illustrate the Concept of Krimi in Ayurveda - Huddar, Shreedevi; Ullagedi, N S; Vaishalee, Kamble (International Research Journal of Ayurveda & Yoga, 2024)
Background: Knowledge of Krimi and its description in Vedas and Ayurvedic Samhitas is very unique and different from the concept of worm in modern medical science. Krimi is a broad terminology in ancient Indian science which encompasses various types of helminths, microorganisms such as bacteria, viruses, fungi, and protozoa causing a large variety of diseases. Materials and Methods: A narrative review was conducted and result was presented under the result. Result and Discussion: Krimi Roga is one among the various diseases which must be paid prime attention in terms of Ayurveda management. Drugs and formulations from herbal sources play key role in management of these helminthic and parasitic infections. A majority of patients being from pediatric age segment, the knowledge of Krimi Roga management may bring a boon to pediatric ailments. Conclusion: Ayurveda believes in Prakriti (specific body constitution of the individual), if we can change the internal environment of the intestine (Kostha) through Apkarshana, Prakriti Vighata and Nidana parivarjana using appropriate drugs as well as enhancing the strength of Agni; then, affinity towards production and multiplication of Krimi may be arrested and hence, the ailments can be treated. Krimi is a condition, affecting all age groups, but children have always been at risk due to their playful activities and lack of maintenance of adequate personal hygiene. Once infected, the entire family may eventually get affected from the infected children.[1] If we consider Drishya Krimi as worm infestation, In India, more than 200 million children are infected on an average with roundworm, hookworm, etc. In Ayurveda, several causes (nidanas) have been mentioned for development of Krimi (microbes/worms) in human body like Ajirna (indigestion in GIT), Adhyashana (eating even when the previous meal has not been digested), Asatmyaahara, Virudhasana, Malinasana (incompatible foods or unhygienic meal habit), Avyayam (sedentary lifestyle), Diwaswapna (sleeping during the daytime), Guru (heavy), Atisnigdha (excessively fatty diet), Atisheet Ahara-Vihara (cold